A different approach to the study of “forced shares” or “legitimas”, based on a comparative study of Spanish and Philippine Succession Law. - De-Torres-Perea, José Manuel (Universidad de Deusto, 2019)
This paper is divided into two different parts. In the first one, a comparative study between the Spanish and Philippine succession law is made. Our basic assumption is that both regulations are parallel, and we focus our analyses on the most relevant differences.First we will study the current Succession Law in the Philippines and in Spain from a positivist perspective, then we will carry out a deeper analysis from another perspective. This is not going to be a traditional study focused on the conflicts between the rights of the forced heirs “legitimarios”, and the liberty of the testator. We offer here a wider perspective based on a philosophic approach. In fact, we would like to contribute something new to the traditional academic debate. Therefore, we will dive deeper into the philosophical arguments to try to find reasons to maintain or reduce or remove the forced shares from our Civil Codes. This research is connected with the need of the Law to act as a tool to achieve certain purposes. In fact, Civil Law could be only a mechanism to solve conflicts and to apply the “ius suum quique tribuendi” principle. However, the lawmaker should also establish the framework in which a society may evolve. This study seeks to identify this framework in the sphere of succession law.
Un análisis alternativo sobre las legítimas a partir del estudio comparado del Derecho de sucesiones español y filipino.
Política de acceso abierto tomada de: https://revista-estudios.revistas.deusto.es/policies/open-access Además editorial da permiso a autor mediante correo electrónico.
Keywords: Herencias y sucesiones - España; Herencias y sucesiones - Filipinas; Sucesión del cónyuge viudo; Spanish and Philippine succession law; Inheritance; Ilegitimate children; Spanish law; Philippine law